Development of a multiplex PCR detection system and identification of binding peptides for human plasmodium species / Chew Ching Hoong - Chew, Ching Hoong (2014)

(untitled)
Malaria is one of the most serious global health challenges. Approximately 3.3 billion people live in malaria-endemic areas and the disease threatens the lives of more than one-third of the world’s population. Malaria is caused by an eukaryotic protozoa Plasmodium and transmitted through the bite of female Anopheles mosquito. The known causative agents of human malaria include Plasmodium vivax, P. falciparum, P. malariae, P. ovale, and recently included P. knowlesi which is recognized as a zoonotic parasite. Malaria is a treatable disease, however the disease can become severe, leading to morbidity if untreated, especially for infections by two potential fatal species, i.e., P. falciparum and P. knowlesi. In the effort to improve the global health status, institution of control and surveillance of malaria, and subsequently enhancing the effectiveness of treatment management, it is critical to develop a rapid, accurate, species-specific/species-sensitive, and cost-efficient diagnostic tool for malaria detection. Therefore, a straightforward single-step multiplex polymerase chain reaction (PCR) targeting five human Plasmodium 18S small subunit ribosomal RNA (ssu rRNA) gene with an internal positive control was developed. This system is specific in detecting all five human malaria parasites with high sensitivity (i.e., 0.025 parasites/μl for P. vivax, 0.027 parasites/μl for P. ovale, 0.15 parasites/μl for P. falciparum, 0.25 parasites/μl for P. knowlesi, and 0.27 parasites/μl for P. malariae), and most significantly enables the simultaneous identification and differentiation of mixed infections at least up to the two-species level without any diagnostic constrains. In addition, the accuracy (sensitivity and specificity) of the detection system were also assured by random blind testing (n=50), clinical screening (n=246), and simulated mixed infections based on clinical samples (n=30) and clone DNA (n=60). All results were in agreement with the results from nested PCR which served as a molecular gold standard. Overall, this ABSTRACT III multiplex system will definitely enhance the accuracy and accelerate the speed in the malaria diagnosis, and improve the efficacy of malaria treatment and control. Plasmodium is an obligate intracellular parasite. Therefore, the understanding of how the parasites enter their host’s cell is of great interest and this offers an attractive target for the development of novel therapeutics. Apical membrane antigen 1 (AMA1) is the most prominent and well characterized malarial surface antigen that is essential for parasite-host cell invasion, i.e., sporozoite into hepatocyte in liver stage and merozoite into erythrocyte in asexual stage. AMA1 has long served as a potent antimalarial drug target and pivotal vaccine candidate. In the present study, recombinant AMA1 proteins of P. knowlesi (rPkAMA1) as well as P. vivax (rPvAMA1) were expressed using Escherichia coli and the binding peptides were identified using a random dodecapeptide phage display library. Phage display is a powerful and cost-effective tool that can be used for assessing the protein-protein interactions. After third rounds of biopanning, two and three phage-displayed binding peptides with affinity to rPkAMA1 and rPvAMA1 respectively were identified and validated through peptide binding assays.